(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe several epidemiological and clinical characteristics of breast cancer patients treated at Nghe An Oncology Hospital. Methods: A descriptive case-series study was conducted on 1,078 women with breast lesions who underwent examination and treatment at Nghe An Oncology Hospital from January 2024 to December 2025. Results: Of 1,078 women with breast lesions, 373 cases were identified as breast cancer, representing 34.6%. The mean age of breast cancer patients was 54.19 ± 12.06 years; the malignancy detection rate increased with age and was highest among women aged ≥70 years (90.56%). Women who gave birth for the first time at ≥ 30 years of age had the highest proportion of breast cancer (57.14%). The group breastfeeding for less than 18 months had a higher proportion of breast cancer than the group breastfeeding for ≥ 18 months (50.92% vs. 28.28%). The proportion of breast cancer was higher among women with early menarche before the age of 15 years (41.83%), postmenopausal status (62.88%), a history of preterm birth (89.66%), and a family history of breast cancer (69.57%). Breastfeeding for less than 18 months was associated with a 2.63-fold higher risk of breast cancer, while early menarche was associated with approximately a 1.5-fold higher risk of breast cancer. Women with a history of preterm birth had a 14.497-fold higher risk of breast cancer than those without a history of preterm birth (OR = 14.497, 95% CI: 5.629–37.335). Similarly, women with a family history of breast cancer had a 4.469-fold higher risk of breast cancer (OR= 4.469, 95% CI: 1.822–10.962). Conclusion: Breast cancer predominantly occurred in older women. Several hormonal, reproductive, and familial factors were associated with breast cancer in this study. These findings may help identify women at higher risk and provide useful information for breast cancer screening and early detection.